(untitled) (Journal of Economic Research & Business Administration, 2017)
In modern conditions of particular relevance and importance of economic integration has gained in the field of agriculture. The article examines the characteristics of integrated structures in agrarian and industrial complex, the role of agro-industrial integration as a source of real investment, improve the competitiveness of the form, the basis of the stabilization and development of agriculture and related industries. In this regard, we identified linkages and relationship problems between adjacent mechanism of its branches involved in the process of product promotion from producer to consumer. Set out the organization of direction, purpose, structure integrated structures, comprising all members of the technological cycle of food production and its promotion to the end consumer, which include agricultural producers, processors and service enterprises, trade. An effective mechanism for integrated structures in agrarian and industrial complex should provide an equivalent exchange between agriculture and industry, the saturation of the food market at the expense of priority and effective development of domestic production.